Efisiensi Produksi Susu dan Kecernaan Rumput Gajah (Pennisetum purpureum) pada Sapi Perah FH dengan Pemberian Ukuran Potongan yang Berbeda - Novianti, J.; Purwanto, B. P.; Atabany, A. (Department of Animal Production and Technology, Faculty of Animal Science, IPB University in associated with Animal Scientist's Society of Indonesia (HILPI), 2014)
Animal feeds with the requirements were given to support production and productivity of livestock. Production and productivity were related with feed consumption and digestibility. Superior grass that was given without cutted causing a lot of wasted parts, so the grass size would be cutted to see an increase in feed consumption and digestibility, and milk production efficiency. The study was conducted on July-October 2013 in Field Laboratory of Animal Husbandry IPB, using four lactation dairy cattle. The research designs were RBSL and analyzed by ANOVA on the four stage treatment with feed consumption, digestibility, and milk production efficiency as observed variables. The results showed that cage condition and environmental could potentially caused mild to moderate stress (THI : 68–90), the size of grass cutted were not significant effect to the digestibility of Dry Material (BK), Crude Fat (LK), Crude Fiber (SK), BETN and TDN but significant effect to the digestibility of crude protein (P<0.05). Digestibility of proteins on cutting size in 5 cm (66.35 ± 5.29%) and 15 cm (67.44 ± 4.83%) higher than controls (63.40 ± 7.65%) and 10 cm (64.61 ± 5.92%). Treatments of the grass cutting were not significant effect to dry material and feces, as well as the efficiency of dry material, crude protein and crude fat were not significantly affect the size of elephant grass clippings. The size pieces of grass were not effect to feed consumption, efficiency and nutrient digestibility of feed but effect on protein digestibility.